Nursing as a career - Chandler, Caroline A. (Caroline Augusta) 1906-; Kempf, Sharon H. (New York Dodd, Mead, 1970)
Describes nursing as a profession, including the possible preparatory tryouts as a volunteer, a candy striper, a nurse's aide, and other training leading to qualification as an R.N.
Bibliography: p. 153-154.
Keywords: Nursing -- Vocational guidance; Nursing -- Vocational guidance